Future-Proofing Arabic Studies: A Strategic Artificial Intelligence Competency Framework for Islamic Higher Education - Albantani, Azkia Muharom; Zainuddin, Nurkhamimi; Swathi, Nair; Sahrir, Muhammad Sabri; Rozak, Abd. (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
The integration of Artificial Intelligence (AI) into higher education is accelerating, yet generic competency frameworks fail to address the unique needs of students in specialized fields, particularly Arabic language learners in Islamic universities. This study addresses this critical gap by proposing a tailored AI Competency Framework designed to equip these students with the skills to navigate an AI-augmented world while upholding their theological and ethical commitments. Employing a digital library research methodology, this paper conducts a systematic literature review and thematic synthesis of scholarship from AI in education and Arabic pedagogy. The resulting framework comprises five interconnected dimensions: (1) Human-Centered Thinking, which grounds technology use in spiritual and intellectual values; (2) AI Ethics, providing a moral guardrail aligned with Islamic principles; (3) AI Techniques and Applications, building practical, tool-specific skills; (4) Domain-Specific AI System Design, fostering an innovative, problem-solving mindset; and (5) AI in Basic Arabic Language Learning, which applies these competencies to core language skills. This framework offers a practical model for universities to integrate AI ethically and effectively, ensuring graduates are not only proficient in Arabic but are also prepared to be responsible stewards of technology in the service of their faith and scholarship.